Measurements of free-free absorption in warm dense aluminium. (4th June 2021) - Hyland, C; White, S; Kettle, B; Irwin, R; Bailie, D; Yeung, M; Williams, G; Heathcote, R; East, I; Spindloe, C; Notley, M; Riley, D
Abstract: Extreme ultraviolet radiation from a high harmonic source has been used to measure the free-free attenuation coefficient and real refractive index of warm dense aluminium, with sample conditions of near solid density and temperature of 0.9 ± 0.23 eV. These were compared to results from the literature, where the measured attenuation coefficients showed some consistency with the modelling and existing data from a previous experiment. The absolute values of the attenuation coefficient were found to reside between the different sets of models for the warm dense matter (WDM) attenuation coefficient, and were found to be more in line with modelling and measurements of the cold opacity from the literature. Novel measurements of the real refractive index of WDM were also achieved—while ambiguity makes these measurements consistent with all the models, they prove useful as a proof-of-concept for future WDM studies.